Selective Electrocatalytic Hydrogenation of Linolenic Acid on Pd/Al2O3 and Pd-Co/Al2O3 Catalysts. (30th November 2010) - Breton, Sylvie; Brisach-Wittmeyer, Anne; Rios Martín, José Julian; León Camacho, Manuel; Lasia, Andrzej; Ménard, Hugues
Abstract : Electrochemical hydrogenation of linolenic acid as a model for polyunsaturated acids was studied on Pd and Pd/Al2 O3 catalysts in acidic and alkaline media. The results are presented in terms of number of double bonds in the polyunsaturated fatty acid and interpreted in terms of the adsorption capacity of the catalysts in these media. The highest hydrogenation yield was obtained with Pd/Al2 O3 at pH 13, in good correlation with the adsorption power of linolenic acid and its first hydrogenation product, linoleic acid, measured in this solution. A preliminary electrochemical hydrogenation study was conducted on Pd/Al2 O3 catalyst containing Co, in the optimum electrolysis conditions, showing a cooperative effect of the noble metals regarding the cis/trans selectivity with preferential formation of cis -oriented monounsaturated compound. All the products were characterized by gas chromatography after derivatization of the samples; fifteen cis-trans isomers of monounsaturated fatty acid which could be identified are presented here.